2015
DOI: 10.3892/mmr.2015.4374
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-590 is an EMT-suppressive microRNA involved in the TGFβ signaling pathway

Abstract: Over the last few decades, the epithelial-to-mesenchymal transition (EMT) has been identified as being involved in a number of aspects of physiological processes and various pathological events, including embryonic development and renal fibrosis. Transforming growth factor-β receptor 2 (TGFβR2) is a widely studied gene, which fulfils a vital role in the TGFβ signaling pathway and exerts a crucial function in the progression of EMT. Previous studies demonstrated that the dysregulation of microRNAs (miRNAs) is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
(39 reference statements)
3
24
0
Order By: Relevance
“…Whereas the resistance of higher‐order cells to reprogramming is not well understood, it is thought to be related to the relative stability of the epigenetic signature of these cells . In this regard, the capability of miR‐590 to enhance cardiomyocyte transdifferentiation is consistent with its previously demonstrated ability to suppress the profibrotic TGFβ signaling pathway, as well as alpha‐smooth muscle actin and COL1 expression associated with myofibroblast generation . These observations are, in turn, reminiscent of the findings of Muraoka et al, who reported that addition of miR‐133 to GMT promotes cardiac reprogramming by directly inhibiting Snail 1 and silencing a fibroblast signature .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Whereas the resistance of higher‐order cells to reprogramming is not well understood, it is thought to be related to the relative stability of the epigenetic signature of these cells . In this regard, the capability of miR‐590 to enhance cardiomyocyte transdifferentiation is consistent with its previously demonstrated ability to suppress the profibrotic TGFβ signaling pathway, as well as alpha‐smooth muscle actin and COL1 expression associated with myofibroblast generation . These observations are, in turn, reminiscent of the findings of Muraoka et al, who reported that addition of miR‐133 to GMT promotes cardiac reprogramming by directly inhibiting Snail 1 and silencing a fibroblast signature .…”
Section: Discussionsupporting
confidence: 77%
“…10 In this regard, the capability of miR-590 to enhance cardiomyocyte transdifferentiation is consistent with its previously demonstrated ability to suppress the profibrotic TGFb signaling pathway, as well as alpha-smooth muscle actin and COL1 expression associated with myofibroblast generation. 35,36 These observations are, in turn, reminiscent of the findings of Muraoka et al, who reported that addition of miR-133 to GMT promotes cardiac reprogramming by directly inhibiting Snail 1 and silencing a fibroblast signature. 26 The procardiomyocyte differentiating properties of miR-590 are likewise consistent with its role in suppressing epithelial-to mesenchymal transition, which has been identified as a morphogenic pathway leading differentiated cells toward a profibrotic state.…”
Section: Discussionmentioning
confidence: 54%
“…The miR-200 family members act as EMT inhibitors by targeting the transcription factor zine finger E-box binding homeobox 1 and 2. 15,21 Yu et al further provided evidence that downregulation of miR-300 is required for EMT initiation and maintenance, and MiR-300 may negatively regulate EMT by direct targeting Twist and therefore inhibit cancer cell invasion and metastasis. 15 EMT includes a series of epithelial plasticity changes in the epithelial and mesenchymal states.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR‐187 inactivates TGF‐β–induced EMT by directly suppressing the expression of SRY‐box 4, 5′‐nucleotidase ecto, and protein tyrosine kinase 6, the upstream effectors of Smad (49). Overexpression of miR‐590 also inhibits EMT by targeting type II TGF‐β receptor (TβRII) in the human kidney cell line (50). We hypothesized that TGF‐β negatively regulates the EMT of trophoblasts by fine‐tuning the expression of miRs.…”
Section: Discussionmentioning
confidence: 99%